Low-Temperature Hydrothermal Systems Response to Rainfall Forcing: An Example From Temperature Time Series of Fumaroles at La Soufrière de Guadeloupe Volcano - de Bremond d’Ars, Jean; Gibert, Dominique (Frontiers in Earth Science, 2022)
We analyze time series of the temperature measured in three fumaroles located at the top of La Soufrière volcano in Guadeloupe. Thanks to the long duration of the records from January to august 2017 and to their short 1-second sampling interval, a multiscale analysis can be performed over several orders of magnitude. We show that, despite their complex and sometimes erratic appearance, the temperature variations observed in the vents contain components highly correlated with rain inputs variations. Some remarkable patterns recurrently appear at different periods and we show that the main temperature variations of mora than 10°C are related to the rainfall intensity. Our results illustrate the importance of external forcing on the otherwise complex and possibly chaotic dynamics of the shallow hydrothermal system of La Soufrière. Their also reveal that a careful analysis of rainfall forcing must be done to be able to draw any conclusion concerning changes caused by the underlying hydrothermal system.